Socio-environmental disaster - Public prosecutor's office, civil defense and the guarantee of rights - Beck, Zilda Januzzi Veloso; Vieira , Gil Correia Kempers; Santos, Alexandre Luís Belchior dos (Seven Editora, 2024)
The present study aims to present a new way of observing risk management and disaster management, seeking to understand better integration between agencies, and in the specific case of this article, the direct relationship between cand the Public Ministry.In this new perspective, the focus is on better guaranteeing fundamental rights, since v deals with disaster actions and is directly linked to the Public Ministry in terms of protecting the fundamental rights of people affected by various forms of socio-environmental disasters. It is worth noting that this new approach has a new way of articulating agencies in favor of better defending the fundamental rights of victims, but with a bias towards including disaster prevention and mitigation actions. DOI:https://doi.org/10.56238/sevened2024.010-014